DEVELOPMENT OF DISTRIBUTION NETWORKS OF CLEAN WATER SYSTEM PERUM JASA TIRTA II, JATILUHUR DISTRICT, PURWAKARTA REGENCY - David H M, Chandra
PJT II Jatiluhur is a State-Owned Enterprise that serves the needs of clean water for industry and domestic in the Jatiluhur area. Domestic services include housing residents and public and social facilities in the vicinity. The production unit serving the Jatiluhur area is IPAM Biki Baru. This service uses water from the Jatiluhur Reservoir. The water from the production is transmitted to the reservoir and will be distributed to the community. Water is distributed from the reservoir to the community using the gravity flow method. PJT II Jatiluhur serves 3605 families from 6 villages where the service level is 20.6%, so development needs to be done. Development is planned over a 20 year planning period. The projected water demand for the next 20 years is 134 liters/second. This plan produces 2 alternative distribution network system paths. In the distribution network of Perum Jasa Tirta II Jatiluhur, a simulation is carried out to determine the water pressure and velocity in the pipe. The simulation is carried out by analyzing the distribution network system design using EPANET 2.0 software. Selection of the best alternative using the Simple Additive Weighting (SAW) method. The chosen alternative is the alternative that best meets the most design criteria. This design distribution network pattern uses a loop pattern, where there are 2 loops in this system. This alternative applies gravity flow so that it does not require a pump. The type of reservoir used is a ground reservoir with a capacity of 1000 m3. The total length of the distribution pipe is 20,046.84 m with a minimum diameter of 150 mm and a maximum diameter of 300 mm. The planned distribution network system has met the hydraulic criteria in the form of a flow velocity of 0.3-2 m/s, a residual pressure of 10-80 mka, and a maximum headloss of 10 m/km. The total cost for the realization of the development of the distribution network system in Jatiluhur District includes procurement costs, preparation work costs, pipe and accessories procurement costs, earthwork costs, pipe installation work costs and accessories Rp 3,878,000,000.00.